MODEL PEMBELAJARAN KOOPERATIF TEKNIK JIGSAW DALAM PENINGKATAN HASIL BELAJAR AKIDAH AKHLAK SISWA MIN 3 TANGERANG SELATAN - Soleha Soleha (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2023)
This study discusses the Jigsaw cooperative learning model implemented at MIN 3 Kota Tangerang Selatan using the survey method with interview and observation techniques to the data sources, namely the head of the madrasa, related teachers and several students. The results of the study prove that the Jigsaw cooperative learning model can improve the learning outcomes of Aqidah Akhlak students at MIN 3, South Tangerang City. The jigsaw technique can be effectively applied in learning when the required steps should be practiced properly and correctly in learning. The steps and their application in learning Aqidah Akhlak at MIN 3 South Tangerang